When the Familial Change: The Impact of Parental Divorce on Children's Learning Styles - Ismi, Khairati; Lahmi, Ahmad; Rahmi, Rahmi (The Magister of Islamic Education IAIN Pontianak, 2025)
The dissolution of a family unit through divorce represents a significant social phenomenon with a profound impact on children's psychological and academic development. The impetus for this study is the rising incidence of divorce in Kajai Village, Padang Pariaman, West Sumatra, Indonesia which has resulted in a range of challenges for children affected by these circumstances. The objective of this study is to examine the impact of parental divorce on children's learning styles and its subsequent effect on their academic performance. A qualitative research approach was adopted, with data collected through observation, in-depth interviewing and document analysis. The research subjects comprised children affected by divorce, their parents, and school personnel, who were selected as key informants for the purposes of this study. The data were subjected to descriptive and analytical analysis in order to gain a comprehensive understanding of the challenges faced by the children. The findings indicate that parental divorce has an impact on children's psychological well-being, which in turn affects their learning styles and academic performance. It is evident that children who have experienced parental divorce often display a range of emotional and behavioural difficulties, including difficulties in maintaining concentration, feelings of sadness, guilt and excessive anxiety. Such difficulties have the potential to have a detrimental impact on their learning outcomes. Nevertheless, some children were able to develop adaptive strategies and demonstrate satisfactory academic achievement. It is of great significance to consider the role of supporting factors, such as family support, the school environment, and individual resilience, in determining the varying responses of children to divorce. This research makes a novel contribution to the field by elucidating the diverse learning styles of children from divorced families, a topic that has been underexplored, and delineating the supporting factors that can facilitate children's adaptation. It is anticipated that the findings of this study will inform the provision of appropriate psychological and academic support for children affected by parental divorce, and serve as a reference for families, schools and policymakers.